RELAKSASI SEBAGAI PROGRAM PENCEGAHAN STRES PADA ANAK - , ISMU CHANDRA KURNIAWATI, Prof.Dr.Sofia Retnowati, M.S.,Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The number of persons with symptoms of stress is increasing significantly worldwide. Stress has always been characterized as symptoms that manifests predominantly in adults, but many studies have shown a large number of children with stress. This study analize the effect of relaxation as a preventive program for stres in children. Experimental design used in this study was a quasi experiment with pretest posttest control group design. Sixty school-age children participated in this study, divided into two group: 30 children at the experimental group, and 30 children at the control group. Experimental group involved in relaxation program which combine 6 psychoeducational sesion, games activity, discussion and role play. Before and after the relaxation program, experimental group and control groupâs stress level were measured by Stress Scale which created by researcher. This scale was made base on stress symptom reported by school-age children at Sharrer & Wenger (2002). Alpha Cronbach for the scale is 0.819. Gain score between pretest and posttest of control and experimental group were analized using an independent sampel t test. Result show that there is no significant difference between control group and experimental groupâs gain score (p>0.05). Relaxation Program was not effective to prevent stress on children.